2022
DOI: 10.1371/journal.ppat.1010673
|View full text |Cite
|
Sign up to set email alerts
|

Active PD-L1 incorporation within HIV virions functionally impairs T follicular helper cells

Abstract: The limited development of broadly neutralizing antibodies (BnAbs) during HIV infection is classically attributed to an inadequate B-cell help brought by functionally impaired T follicular helper (Tfh) cells. However, the determinants of Tfh-cell functional impairment and the signals contributing to this condition remain elusive. In the present study, we showed that PD-L1 is incorporated within HIV virions through an active mechanism involving p17 HIV matrix protein. We subsequently showed that in vitro produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…We showed that bioactive LPS loaded on CD14 + virions could activate NF-κB and IRF3 in a TLR4 reporter cell line, and in THP-1 monocytes, it triggered the secretion of TNF-α and CCL5. While others have described the impact of incorporated immunoregulatory proteins on cell signaling ( 26 28 ), our work highlights a pivotal role for CD14 in allowing virions to function as a shuttle for bioactive molecules like LPS and eliciting inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that bioactive LPS loaded on CD14 + virions could activate NF-κB and IRF3 in a TLR4 reporter cell line, and in THP-1 monocytes, it triggered the secretion of TNF-α and CCL5. While others have described the impact of incorporated immunoregulatory proteins on cell signaling ( 26 28 ), our work highlights a pivotal role for CD14 in allowing virions to function as a shuttle for bioactive molecules like LPS and eliciting inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Most interesting was the resulting activation of the transcription factors nuclear factor kappa B (NF-κB) and nuclear factor of activated T cells, which activated HIV-1 long-terminal repeat-driven gene expression ( 27 ). More recently, it was shown that HIV-1 can incorporate the immune checkpoint ligand, programmed death-ligand 1 (PD-L1) ( 28 ). Conferred with an immunoregulatory ability, HIV-1 virions with incorporated PD-L1 impaired follicular helper T cell proliferation and cytokine secretion, resulting in reduced IgG1 secretion by autologous B cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, both virions and infected cells were recently shown to display high levels of PD-L1, an immune check point ligand that could induce exhaustion of CD8 + T cells. 118 PD-L1 expression differs at the specificity level 119 and could thus be a mechanism of preferential persistence.…”
Section: Host Cell Factors Influencing Persistencementioning
confidence: 99%
“…Previously reported showed that KDM5A can induce PD-L1 expression [33,34] that may suppress the immune response for immune escape during HIV-1 infection [35][36][37][38][39]. The other KDM5, KDM5B, has been identified to suppress immune sensing from the STING-GAS signaling [40] and RIG-I signaling [41] to decrease innate immunity and antiviral responses.…”
Section: Introductionmentioning
confidence: 99%
“…KDM5A is one of the KDM5 demethylases (KDM5 A, B, C, and D), which catalyzes demethylation from H3K4me3 to H3K4me2 and then to the final product H3K4me1 [29-32]. Previously reported showed that KDM5A can induce PD-L1 expression [33, 34] that may suppress the immune response for immune escape during HIV-1 infection [35-39]. The other KDM5, KDM5B, has been identified to suppress immune sensing from the STING-GAS signaling [40] and RIG-I signaling [41] to decrease innate immunity and antiviral responses.…”
Section: Introductionmentioning
confidence: 99%